Long-term Recovery Patterns of Olfactory Function after Trans-sphenoidal Approach with Nasoseptal Flap Elevation - Koo, Bon Min; Jeong, Jong In (International Archives of Otorhinolaryngology, 2023)
Introduction Nasoseptal flap is widely used in reconstruction of the skull base to prevent cerebrospinal fluid leakage after surgery for skull base lesions. There has been a debate on whether more severe olfactory dysfunction occurs after nasoseptal flap elevation than the conventional trans-sphenoidal approach.Objective To compare the long-term recovery patterns associated with nasoseptal flap and the conventional trans-sphenoidal approach.Methods The subjects were divided into the conventional trans-sphenoidal approach group and the nasoseptal flap elevation group. We followed up self-reported olfactory score using the visual analogue scale and threshold discrimination identification (TDI) score of the Korean Version of the Sniffin Stick test II for 12 months, with olfactory training.Results The study included 31 patients who underwent the trans-sphenoidal approach. Compared with preoperative status, the mean visual analogue scale and TDI scores in the conventional trans-sphenoidal approach group recovered 2 months postoperatively, while in the nasoseptal flap elevation group the visual analogue scale and TDI scores recovered 6 months and 3 months after surgery, respectively. Twelve months after surgery, the visual analogue scale and TDI scores in the conventional trans-sphenoidal approach group were 9.3 ± 0.5 and 28.5 ± 4.3, while those from the nasoseptal flap elevation group were 8.9 ± 1.5 and 27.2 ± 4.7 (p = 0.326; 0.473). Only one of the patients in the nasoseptal flap elevation group had permanent olfactory dysfunction.Conclusion The olfactory function recovered more gradually in the nasoseptal flap elevation group than in the conventional trans-sphenoidal approach group, but there was no difference between the two groups after 6 months.
Keywords: trans-sphenoidal approach; nasal septal flap elevation; pituitary adenoma; olfactory function